Vaccine Development Against Leishmania donovani - Das, Amrita; ALI, NAHID (Frontiers in Immunology, 2012)
Visceral leishmaniasis (VL) caused by Leishmania donovani and Leishmania infantum/ chagasi represents the second most challenging infectious disease worldwide, affecting nearly 500,000 people and 60,000 deaths annually. Zoonotic VL (ZVL) caused by L. infantum is re-emergent canid zoonoses which represents a complex epidemiological cycle in New world where domestic dogs serve as reservoir host responsible for potentially fatal human infection where dog culling is the only control measure for eliminating reservoir host. Lifelong immunity in human against reinfection has motivated several attempts in developing prophylactic vaccines against the disease but very few have progressed beyond experimental stage. Absence of any licensed vaccine along with high toxicity and increasing resistance to the current chemotherapeutic drugs has further complicated the situation in endemic regions of the world. Advances in vaccinology, including recombinant proteins, novel antigen-delivery systems/adjuvants, heterologous prime-boost regimens and strategies for intracellular antigen presentation, have contributed to recent advances in vaccine development against VL. Attempts to develop an effective vaccine for use in domestic dogs in areas of canine VL should be pursued for preventing human infection. Studies in animal models and human patients have revealed the pathogenic mechanisms of disease progression and features of protective immunity. This review will summarize the accumulated knowledge about pathogenesis, immune response and prerequisites for protective immunity against human VL. Authors will discuss promising vaccine targets, their developmental status and future prospects in a quest for rational vaccine development against VL. In addition, several challenges such as safety issues, a renewed and coordinated commitment to basic research, preclinical studies and trial design will be addressed to overcome the problems faced in developing effective vaccines against VL.